Received empowering knowledge and associated factors among patients with cancer: A cross-sectional multicentre study - Arffman, Heli; Siekkinen, Mervi; Leino-Kilpi, Helena; Pasanen, Miko; Virtanen, Heli (ELSEVIER SCI LTD, 2026)
Purpose: This study aimed to analyse the knowledge received by patients with cancer and to examine its association with sociodemographic, illness-related, and psychological factors, as well as health-related quality of life (QOL).
Methods: This cross-sectional multicentre survey included patients (n = 350) undergoing chemotherapy, radiotherapy, or post-treatment follow-up at two Finnish university hospital outpatient clinics. Data were collected between February and September 2019. The survey employed the Received Knowledge of Hospital Patient scale (RKhp), General Self-Efficacy Scale (GSE), Short Warwick-Edinburgh Mental Well-Being Scale (SWEMWBS), and the 15D Quality of Life Questionnaire. Data were analyzed using multivariate statistical methods.
Results: Patients reported receiving the most knowledge in the biophysiological domain of empowerment, followed by functional and experiential domains, whereas knowledge regarding financial, social, and ethical aspects was received the least. Several sociodemographic factors were significantly associated with received knowledge. Patients with higher education, and those who were single or employed, reported receiving less knowledge. In contrast, illness-related factors showed little or no association with received knowledge. Of the psychological factors, only positive mental well-being was associated with higher levels of received knowledge. No associations were found between received knowledge and self-efficacy or QOL.
Conclusions: The findings highlight the need to improve patient education, particularly in psychosocial, ethical, and financial aspects, to better address patients' individual knowledge needs. This study offers insights for clinical practice and future research aiming to enhance patient-centered education.